ACADEMIC CHALLENGES OF TURKISH INTERNATIONAL STUDENTS IN PAKISTAN: A QUALITATIVE STUDY - Ersan, Kevsernur; Khalil, Ayesha (PEOPLE: International Journal of Social Sciences, 2019)
Studying abroad is quite interesting for the students who wish to learn new cultures and languages. Some students prefer to go abroad for higher education so they can also get to experience different culture, people, languages and learn many other things about the host country. When students choose to go abroad for higher education, they are faced with many challenges in education. Every country has their own unique education style and it is quite challenging to adjust to different academic teaching style and new learning environment. This particular study examines the issues surrounding Turkish international students experience of higher education in Pakistan. Qualitative methodology was employed to penetrate into the topic under investigation. Semi-structured in-depth interviews were conducted with a sample of 6 Turkish students. By using Thematic Analysis five themes emerged: (a) language barrier, (b) un-coperative classfellows, (c) expectations from teachers, (d) different study methods, (e) inability to express in class. The findings both supports and contribute new aspects to the knowledge of this experience. A number of recommendations are made to enable those who come to Pakistan from Turkey to adapt and make the transition necessary in order to enhance their experience of pursuing education in a foriegn country.